2012
DOI: 10.1007/s12262-012-0771-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Extrapulmonary Oligometastatic Non-small Cell Lung Cancer

Abstract: The prognosis of metastatic non-small cell lung cancer (NSCLC) is poor, and platinum-based chemotherapy improves the median survival for only a few months. A subgroup of patients with oligometastatic disease may benefit from surgical resection, but only very limited data are available to date. We conducted a retrospective review of all patients with synchronous extrapulmonary oligometastatic NSCLC undergoing surgical resection in our department. Data regarding medical history, histology, number of metastases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…These findings are consistent with previous reports (4,24). Kaplan-Meier analysis revealed that adenocarcinoma with molecular-targeted therapy had a better prognosis compared with squamous carcinoma and adenocarcinoma without molecular-targeted therapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 93%
“…These findings are consistent with previous reports (4,24). Kaplan-Meier analysis revealed that adenocarcinoma with molecular-targeted therapy had a better prognosis compared with squamous carcinoma and adenocarcinoma without molecular-targeted therapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------supporting
confidence: 93%
“…The resection of solitary cutaneous metastasis was associated with long-term survival; solitary synchronous brain and adrenal metastasis were associated with 5-year survival rates of 12 and 22%, respectively [14]. In another study by Plönes et al, 46 patients (82.1%) suffered from brain metastasis, four patients (7.1%) had adrenal gland metastasis, four patients had soft tissue metastasis (7.1%), and two patients (3.7%) had bone metastasis [15]. All patients underwent anatomical surgical excision for the primary tumor site; and for the metastasis, the resection was macroscopically and microscopically completed in all cases [15].…”
Section: A General Considerationmentioning
confidence: 95%
“…Similarly, it is also known that the tumors which N status is low may be metastatic. In the study by Plönes et al, 56 patients with distant metastasis were evaluated; 30 patients (53.6%) had N0 disease, 18 (32.1%) patients had N2, and one patient (1.8%) had N3 disease [15]. In another study by Mordant et al, 49% of metastatic NSCLC patients had N0 disease, and 33% of the patients had N2 disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Plönes et al found significantly different median survival (MS) for NSCLC patients by location of OM: 23.4 months for soft tissue metastases, 16.7 months for brain, 9.5 months for AM, and 4.3 months for bone metastases (p<0.005). 28 Local relapse (LR) occurred on average in 14% (n=8; range 0-25%), with one additional study describing no LR after R0/R1 resections, but 11% local progression after an R2 resection. 29 LRs have been associated with capsular invasion 26 and intraoperative tumor rupture, 30 but not particularly impacted by postoperative RT.…”
Section: Median Survivalmentioning
confidence: 99%
“…27 All should have pathologic confirmation of the primary, 25 and, in the case of synchronous AM, determination of mediastinal LN status, 19,24,28,50 especially nodes with a short axis dimension of 1-1.5 cm. 20,26 While surgical or ablative therapy in the setting of N2 intrathoracic nodes remains controversial, 33,71 the presence of extra-adrenal OM which can also be approached radically does not appear to be a contraindication.…”
Section: Recommendationsmentioning
confidence: 99%